Faktor-Faktor Yang Mempengaruhi Kinerja Perusahaan Pada Perusahaan Jasa Tahun 2015-2018 - Kevin, Merry Susanti (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study was to examine the effect of leverage, firm size, total asset turnover, board size, liquidity, and firm age on firm performance in Property, Real Estate, and Building Construction sectors listed in Indonesia Stock Exchange for the period of 2015-2018. This research used 58 companies that were selected using purposive sampling method of total 232 data in four years and were analyze using data panel regression in Eviews 10 with fixed effect model to test the hypothesis. Dependent variables in this research are Return on Assets (ROA) and Return on Equity (ROE). The partial tests of total asset turnover have a positive effect on firm performance. Liquidity have a negative effect on firm performance. In contrast, leverage, firm size, board size, and firm age have no effect on firm performance.